Uji Korelasi dan Sidik Lintas Beberapa Karakter Pepaya Terhadap Ketahanan Antraknosa - Siti Hafsah (Jurnal Agrista, 2008)
The Correlation Test and Path Analysis of Antrachnose Disease Resistance of Pepaya ABSTRACT. The aims of this research were to estimate the correlation coefficient among agronomic traits on antrachnose disease resistance of papaya and evaluate the direct and indirect effects of those traits on antrachnose disease resistance of papaya. The result showed that fruit length, flesh thickness, percent symptoms had positive correlation to severity disease and dry of fruit ripe, percent TSS, flesh fimness had negative correlation to severity disease. Path analysis applied an agronomic and resistance character on antachnose disease resiistance indicated that antrachnose disease resistance was directly affected by percent symptom. The largest compound path coefficient of agronomic traits on antrachnose disease resistance that percent TSS and flesh thickness via percent symptom.